Soluble suppression of tumorigenicity associated to post-procedural no-or-slow-reflow phenomenon in ST-elevation myocardial infarction. (3rd October 2022) - Sondergaard, F; Beske, R; Frydland, M; Helgestad, O; Jensen, L O; Holmvang, L; Engstroem, T; Moeller, J E; Hassager, C
Abstract: Background: Over the last decades, the prognosis for patients with ST-elevation myocardial infarction (STEMI) has improved due to primary percutaneous coronary intervention (pPCI). However, no-or-slow-reflow phenomenon after pPCI constrains this benefit. Suppression of tumorigenicity (sST2) is released from vascular endothelial cells in response to myocyte stretch and increased sST2 level in the initial phase of STEMI is a useful prognostic biomarker for predicting mortality and heart failure (HF). Purpose: To explore the association of sST2 with post-procedural no-or-slow-reflow phenomenon in patients with STEMI. Method: During a 1-year period in 2015/2016, the study included consecutive STEMI patients from two heart centers who underwent acute coronary angiography (CAG). Blood samples including sST2 levels were collected at admission and before angiography and/or revascularization. Post-procedural coronary flow was assessed according to thrombolysis in myocardial infarction (TIMI) classification for STEMI. We divided patients into two groups: TIMI 0, 1 and 2 as no-or-slow-reflow, and TIMI 3 as normal reflow. Both troponin I and troponin T were used and therefore combined and grouped into 10th percentile levels. The association between sST2 and TIMI flow was explored using multiple logistic regression adjusted for age, gender, hypercholesterolemia, diabetes, hypertension, cardiogenic shock, time from onset of symptoms to CAG, and troponin levels. Results: In total, 1, 789 consecutive patients with verified STEMI and available TIMI flow classification were included in the analysis. Of these, 1, 693 (94.6%) classified as normal reflow and 96 (5.4%) as no-or-slow-reflow. The proportion of male sex was similar (1, 253 (74%) vs 67 (70%), p=0.36) in the two groups. No-or-slow-reflow patients were older (median 68 years (IQR 57–75) vs median 63 years (IQR 54–72), p=0.02) and more likely to develop cardiogenic shock (22 (23%) vs 146 (8.6%), p<0.001). The troponin level was similar in the two groups (no-reflow: 5.50 (2.00, 8.00) vs normal reflow: 5.00 (3.00, 7.00), p=0.38). In the regression model, sST2 was independently associated with post-procedural no-or-slow-flow (two-fold sST2 increase: OR 1.37 (1.09, 1.70, p=0.006)). Conclusion: In patients with STEMI, sST2 level at admission before coronary angiography is associated with the post-procedural no-or-slow-reflow phenomenon. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Righospitalets Forskningsfond AND Lundbeck Foundation